Análise da viabilidade econômico financeira para a instalação de um sistema fotovoltaico em uma empresa de cal na cidade de Baraúna-RN - Rebouças, Cristiana Carla de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
His study aimed to analyze the economic and financial viability of installing a photovoltaic solar system connected to the electric grid, in the administrative building of a virgin lime production company, located in Baraúna-RN. Therefore, an exploratory research was conducted through case study, with a descriptive and qualitative approach. Regarding the viability analysis of the project, the photovoltaic system's power generation capacity over a 25-year period was considered, equivalent to the lifetime of the plates, and the solar radiation index at the installation site of the panels was also considered as well as your income. For the financial economic analysis, we used the Minimum Attractiveness Rate (TMA) which was based on the current Selic rate, the Net Present Value (NPV), the Internal Rate of Return (IRR), and the discounted Payback. The tariff considered was the value estimated by COSERN of 8.47%, average of the last five years. The results of the case study show us that the panel installation project is feasible, considering that the Payback is 4 years and the NPV in the fifth year of investment is positive.
Monografia
Keywords: Viabilidade econômico-financeira; Sistema fotovoltaico; Payback; Economic and financial viability; Photocoltaic system; Payback; ENGENHARIAS::ENGENHARIA DE PRODUCAO